Effect of Curcumin on Cortisol, Catalase and Nerve Growth Factor Expression Level in Animal Model of Induced Multiple Sclerosis - Laleh Mavaddatiyan; Shiva Khezri; Seyyed Meysam Abtahi Froushani (مجله دانشگاه علوم پزشکی گرگان, 2022)
Background and Objective: Multiple sclerosis (MS) is a common neurological disease that increases oxidative stress and causes immune system disorders. Curcumin is the active component of turmeric with anti-inflammatory properties. This study was conducted to determine the effects of curcumin on cortisol, catalase, and nerve growth factor (NGF) expression in an animal model of MS. Methods: This experimental study was conducted on 30 female Wistar rats. Experimental autoimmune encephalomyelitis (EAE) was chosen as an experimental model of MS. The rats were divided into 3 groups of 10, including a healthy control group, an affected group, and a group treated with curcumin. The disease was induced by immunization of rats with homogenized guinea pig spinal cord and Freund's complete adjuvant. Then, the immunized animals were allocated into two equal groups. Treatment with curcumin (100 mg/kg daily) was started 12 days after the immunization when the rats showed the first symptoms of neurologic disability. The treatment was continued until day 24 post-immunization. Simultaneously, the EAE group received the medicine solvent (distilled water). Finally, the rats' weights as well as cortisol, catalase, and NGF levels were measured in the study groups. Results: Curcumin significantly increased the level of cortisol to a level equal to that of healthy rats (P<0.05). It also significantly increased the expression of NGF and reduced the amount of catalase in the affected rats (P<0.05). The curcumin administration significantly increased the overall weight of rats with MS but had no significant effect on the spleen weight of the treated rats. Conclusion: Curcumin can be beneficial for treating EAE by reducing the destructive effects of oxidative damage and increasing NGF.